Traditional Weaving and Handloom Practices as a Tourism Development Tool: A study of Umden-Diwon Village, Ri Bhoi District, Meghalaya - Makri, Wanpynsuk; Kulshreshtha, Dr. Sharad Kumar (Turizam, 2026)
In Meghalaya, 80 % of the population lives in rural areas, and many of the residents are involved in various economic activities, which is essential to improve their quality of life. Apart from agricultural activities, the handloom sectors are considered important by many rural communities. The purpose of the study is to assess the current scenario of the traditional handloom practices and to examine the perception of local communities of Umden-Diwon Village on integrating traditional handloom practices as a tourism development tool. The study adopted a mixed-method approach, using a structured questionnaire and interviews. The result of the study reveals that the majority of the weavers’ communities see tourism as a tool for development, in the context of socioeconomic growth, cultural preservation and community empowerment. Integration of the traditional handloom practices with the growth of touristic activities within the local community is also very challenging. Therefore, the study recommended that it is very important in creating policies that support sustainable tourism development, long-term cultural heritage, preservation and community empowerment in the region.